Patterns of consumption and digital entertainment among young people: A sociological approach to monetary spend on audiovisual digital platforms, content creators and gaming - Calderón Gómez, Daniel; Gómez Miguel, Alejandro (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2023)
This article studies the digital leisure activities of young people in Spain, focusing on their digital consumption habits and spending patterns on subscription-based digital platforms for audiovisual content, on content creators (subscriptions, donations) and video games (purchases, subscriptions and microtransactions). The study employed a quantitative methodology and univariate and bivariate analysis, which were complemented by a multinomial logistic regression model. Gender, age, educational level, employment situation, material deprivation, access to technology and digital leisure frequency were included as control variables. In terms of the main findings, the widespread adoption of paid services stands out, as well as some associated risks, such as increased and uncontrolled spending (particularly in relation to content creation and microtransactions in gaming practices) among more vulnerable social groups (lower educational levels, higher material deprivation).